MEDITATION AND RITUAL IN NEO-CONFUCIAN, TRADITION - Anne Ch'ien (Journal of Dharma, 2020)
Compared with the study of the meditative traditions in Buddhism and Hinduism, American scholarly research on medita- tion in Chinese Neo-Confucianism has only begun to flourish. The .following essay is intended as a general introduction to the problem of quite-sitting (ching-tso) as a meditative form of Neo- Confucian self-cultivation which, as will be shown later, is related to the Neo-Confucian concept of action as ritual.